Harbour Porpoises Are Flexible Predators Displaying Context‐Dependent Foraging Behaviours - Johanna Stedt; Héloïse Hamel; Sara Torres Ortiz; Jakob Højer Kristensen; Magnus Wahlberg (Ecology and Evolution)
ABSTRACT Opportunistic mobile predators can adapt their behaviour to specific foraging scenarios, allowing them to target diverse prey resources. An interesting example is the harbour porpoise (Phocoena phocoena), a marine mammal with a huge energy demand feeding on a large variety of fish, squid and shrimps. Little is known about the foraging behaviour of harbour porpoises, as observations of wild specimens are notoriously difficult to obtain. In this study, foraging was identified in almost 60% of videos from UAV recordings in Danish coastal waters during daylight hours. Observations reveal them to be flexible predators, foraging on both single fish and schools of fish, as well as individually and in groups of varying sizes. We argue that some of the observed behavioural adaptations and context‐dependent strategies for prey capture are based on information transfer and social learning. Our results provide unprecedented insights into the foraging behaviour of an opportunistic mammalian predator. Furthermore, this study highlights the importance of porpoises having access to coastal areas for energy acquisition, where they are in conflict with anthropogenic disturbances such as fisheries with the risk of bycatch.